Proton magnetic resonance spectroscopy changes in the brainstem in patients after mild traumatic brain injury with loss of consciousness - Ružinák, R; Bittšanský, Michal; Martiníková, Martina; Nosáľ, Vladimír; Kantorová, Ema; Ballová, Jana; Turčanová Koprušáková, Monika; Hnilicová, Petra; Grendár, Marián; Dušenka, Róbert; Kolarovszki, Branislav; Zeleňák, Kamil; et al. (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2022)
INTRODUCTION: Loss of consciousness (LOC) is used as a diagnostic feature of mild traumatic brain injury (MTBI). However, only 10% of concussions result in LOC. There are only a limited number of in-vivo studies dealing with unconsciousness and structural and functional integrity of the brainstem in patients with MTBI. The aim of our pilot study was to assess the sensitivity of proton magnetic resonance spectroscopy (1H-MRS) to detect metabolic changes in the brainstem in patients after MTBI with unconscioussness. METHODS: Twenty-four patients (12 with LOC, and 12 without LOC) within 3 days of MTBI and 19 healthy controls were examined. All subjects underwent single-voxel 1H-MRS examination of the upper brainstem. Spectra were evaluated using LCModel software. Ratios of total N-acetylaspartate (tNAA), total choline-containing compounds (tCho) and glutamate plus glutamine (Glx) to total creatine (tCre) were used for calculations. RESULTS: We found a significant decrease in tNAA/tCre and tCho/tCre ratios in the patient group with LOC when compared with the control group of healthy volunteers (P=0.002 and P=0.041, respectively), and a significant decrease in the tNAA/tCre ratio in the LOC group when compared with patients without LOC (P=0.04). Other metabolite ratios in the brainstem did not show any significant group differences. CONCLUSION: Our findings indicate that decrease of tNAA/tCre ratio in the upper brainstem using single-voxel 1H-MRS may provide a potential biomarker for MTBI associated with LOC.
Keywords: Proton Magnetic Resonance Spectroscopy; komoce mozku; bezvědomí; Brain Stem; lidé; Brain Concussion; Unconsciousness; Pilot Projects; mozkový kmen; pilotní projekty; protonová magnetická rezonanční spektroskopie; Humans